2022
DOI: 10.1039/d1cp05570d
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation of helium in PuOx and the role of americium

Abstract: The high alpha-activity of plutonium dioxide (PuO2) results in significant ingrowth of radiogenic helium (He) in the aged material. To safely store/dispose PuO2 or use in applications such as space...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…The most stable site for He in defect-free PuO 2 was determined to be the Octahedral Interstitial Site (OIS), in agreement with available literature. 18,22,43 The incorporation energy for He at an OIS was 1.7 eV which is within the range of values (0.4 18 –2.73 16 eV) calculated via DFT studies available within the literature. From here on, when interstitial He is referred to, it is at an OIS.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The most stable site for He in defect-free PuO 2 was determined to be the Octahedral Interstitial Site (OIS), in agreement with available literature. 18,22,43 The incorporation energy for He at an OIS was 1.7 eV which is within the range of values (0.4 18 –2.73 16 eV) calculated via DFT studies available within the literature. From here on, when interstitial He is referred to, it is at an OIS.…”
Section: Resultssupporting
confidence: 77%
“…Next, helium incorporation at defect sites were investigated. It was found that helium is most stable in V Pu sites with an incorporation energy of 0.19 eV, which is in good agreement with the 0.16 eV DFT calculated value from Neilson et al 22 . Favourable helium incorporation in actinide vacancies has also been found in UO 2 44 and ThO 2 .…”
Section: Helium Incorporationsupporting
confidence: 88%
See 2 more Smart Citations
“…The fluorite configuration further allows the formation of vacant octahedral interstitial sites located at the center and middle of the edge of the cubic system thus accommodating a relatively open crystal structure. 154 This property particularly provides a strong resistance of the ceramic to radiation damage and good stability in the nuclear reactor, without deformation of the structure and surrounding cladding that could lead to migration of matter in the exchangers.…”
Section: Impact Of the Nanoparticle Size On The Crystalline Structure...mentioning
confidence: 99%